2022
DOI: 10.1002/pa.2807
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility on the reputation of universities within developing countries: Evidence from Jordan

Abstract: This paper aims to investigate the impact of corporate social responsibility on organizational reputation in Jordanian universities. Quantitative approach was adopted; electronic survey was employed wherein there was distribution of questionnaires to a sample of employees selected through a simple random approach. The sample was made up of a total of 340 employees based within both private and public universities in Jordan. This current study was founded upon the assumption that the commitment of organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…Moreover, of the 331 respondents, most of them (85 %) were undergraduates. It has been observed that since the September 11 attacks in the United States international students, especially those of Arab origins enroll in Malaysian universities (Alzubaidi, Rechards, 2010;Chin, 2019;Nadeem et al, 2020;Sirat, 2008). Although the respondents were enrolled in various faculties of IUKL, most of them were enrolled in the Faculty of Engineering with a sizeable number of them enrolled in faculties of business and information technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, of the 331 respondents, most of them (85 %) were undergraduates. It has been observed that since the September 11 attacks in the United States international students, especially those of Arab origins enroll in Malaysian universities (Alzubaidi, Rechards, 2010;Chin, 2019;Nadeem et al, 2020;Sirat, 2008). Although the respondents were enrolled in various faculties of IUKL, most of them were enrolled in the Faculty of Engineering with a sizeable number of them enrolled in faculties of business and information technology.…”
Section: Discussionmentioning
confidence: 99%
“…Reputation is described as the collective representation of multiple constituencies, the image of a company [or organisation] built up over time and based on a company [or organisation's] identity programs, its performance and how constituencies have perceived its behaviour (Argenti, Druchenmiller, 2004;Pires, Trez, 2018). Reputation is also described as intangible (Abdullah, Abdul Aziz, 2013;Rindova, Martins, 2012;Taamneh et al, 2022;Shah, Abdullah, 2016). Thus, it is very difficult to measure.…”
Section: Concept Of Reputationmentioning
confidence: 99%
“…Therefore, integrating CSR into business strategies and operations can be a valuable tool for organizations seeking to improve their performance and reputation. From this perspective, social responsibility can be a strategic tool that, coupled with managerial accounting and adequate sustainability reporting, leads to a good reputation and sustainable financial results [11][12][13][14][15][16][17]20,21,111,112].…”
Section: Discussionmentioning
confidence: 99%
“…Reputation is also described as intangible (Abdullah, Abdul Aziz, 2013;Rindova, Martins, 2012;Shah, Abdullah, 2016). "Thus, it is very difficult to measure" (Taamneh et al, 2022;Shah, Abdullah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CEOs perceive the importance of reputation management with utmost importance. A study found that 90 % of CEOs prove that stakeholders especially customers, will consider corporate reputations importance when they decide to purchase a product or service (Abdallah, Abdul Aziz, 2013;Taamneh et al, 2022). According to Global Corporate Reputation Index (GCRI, 2020: 2, 7), reputation has a different importance to organisations.…”
Section: Introductionmentioning
confidence: 99%